2023
DOI: 10.1039/d3qi00230f
|View full text |Cite
|
Sign up to set email alerts
|

Structure and optical property evolution in PbM(PO4)X (M = Zn, Sn; X = halogen): SHG effect and birefringence

Abstract: Four new phosphates, namely, PbZn(PO4)F (1), PbSn(PO4)Cl (2), PbSn(PO4)Br (3) and PbSn(PO4)I (4), were achieved by hydrothermal and solid-state methods successfully. PbZn(PO4)F (1) was crystallized in a polar space group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Recently, Sb 3+ /Sn 2+ -polyhedron with stereochemically active lone pair (SCALP) electrons have shown great potential in the construction of excellent nonlinear and birefringent crystals. [21][22][23][24] For example, CsS-bF 2 SO 4 [25] and K 2 Sb(P 2 O 7 )F [26] exhibit large SHG response of 3.0 and 4.0 × KDP, and Sn 2 PO 4 I shows the birefringence as large as 0.664 at 546 nm. [27] Hence, it is urgent to solve the problem encountered in crystal growth of Sb 3+ -containing compounds.…”
mentioning
confidence: 99%
“…Recently, Sb 3+ /Sn 2+ -polyhedron with stereochemically active lone pair (SCALP) electrons have shown great potential in the construction of excellent nonlinear and birefringent crystals. [21][22][23][24] For example, CsS-bF 2 SO 4 [25] and K 2 Sb(P 2 O 7 )F [26] exhibit large SHG response of 3.0 and 4.0 × KDP, and Sn 2 PO 4 I shows the birefringence as large as 0.664 at 546 nm. [27] Hence, it is urgent to solve the problem encountered in crystal growth of Sb 3+ -containing compounds.…”
mentioning
confidence: 99%
“…Based on the current study of Sb‐based phosphates, we found that most of the P atom are tetra‐coordinated, such as [PO 4 ], [HPO 3 ], [PO 2 F 2 ] [41–43] . Among them, only K 2 Sb(P 2 O 7 )F, Sb 0.5 Fe 0.5 (P 2 O 7 ), Sb 0.5 In 0.5 (P 2 O 7 ), ( α, β )‐Sb 2 (P 2 O 7 ) 2 contain [P 2 O 7 ] groups.…”
Section: Resultsmentioning
confidence: 98%
“…Twenty‐three crystals are present in this system, [13, 80–109] as far as we know. Among them, ten crystals exhibit large optical anisotropy with birefringence greater than 0.10@1064 nm, especially Sn 2 PO 4 X (X=F, Cl, Br, I), whose optical anisotropy was studied in detail by Pan and Zou, et al.…”
Section: Resultsmentioning
confidence: 99%
“…Mao, et al. synthesized Ba 3 Sb 2 (PO 4 ) 4 through mild hydrothermal reactions, [101] and it crystallized in the centrosymmetric space group C 2/ c . The 1D chains composed of isolated SbO 4 and PO 4 can be seen in Ba 3 Sb 2 (PO 4 ) 4 (Figure 15a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation